(untitled) (Global Journal of Medical Research, 2018)
The objective of this study was to provide physiological values on the growing miniature pigs in isolator. Measurements were taken of each miniature pigs’ body weight, temperature, hematological and serum biochemistries, and heart rate. The miniature pigs were divided into 2 groups. The piglet group (n = 8), consisting of animals approximately 4 weeks old and weighing 5 to 7 kg, were used to obtain normal physiological values at 6, 10, 14, 18, and 22 weeks of age. The adult group (n = 8), which consisted of animals approximately 40 weeks old weighing 19 to 21.3 kg, was used to obtain normal physiological values for miniature pigs at 43, 47, 51, 55, and 59 weeks of age. None of the animals displayed abnormal behavior or symptoms while they were bred in the isolators. The weight of every animal that was bred in an isolator gradually increased.